Innovation in animation-based learning media with local wisdom: a strategy for character education in students in the digital era - Kartini, Dedeh; Fitriasari, Susan; Bestari, Prayoga (Universitas Ahmad Dahlan, 2025)
This article examines the need for innovation in animation-based learning media grounded in local wisdom as a strategy to strengthen character education in the digital era. The research problem addressed is the lack of culturally relevant digital learning media that effectively instills character values in students. This study employs a qualitative descriptive approach through a systematic literature review of 15 peer-reviewed journals selected based on relevance, publication credibility, and focus on local wisdom integration in education. Content analysis was used to categorize themes related to the role of animation in enhancing student engagement, cultural identity, and character development. The findings indicate that animation-based learning media incorporating local wisdom can improve students' understanding of cultural heritage while fostering values such as cooperation, mutual respect, and responsibility. Specifically, studies reviewed show that students exposed to culturally relevant animations demonstrate increased interest in learning, stronger emotional connections to the content, and improved retention of moral lessons. Furthermore, this approach supports the preservation of cultural values amidst globalization by reinforcing pride in local traditions and encouraging intergenerational knowledge transfer. Despite these benefits, challenges remain in terms of accessibility, digital literacy among educators, and the need for collaboration between cultural experts and multimedia developers. Future research should explore empirical case studies measuring the direct impact of local wisdom-based animation on students' character formation. This innovation presents a viable solution for developing a generation that is academically proficient and deeply rooted in ethical and cultural values.